Social image of Physical Education students from Juiz de Fora Federal University - Marcelo Moraes e Silva (Journal of Physical Education (Maringá), 2008)
The current study aims at analysing the social image of Physical Education (PE) students from Universidade Federal de Juiz de Fora – Brazil. 174 students answered a questionnaire about PE. Results pointed out an increasing participation in physical activities outside school comparing to a decrese in PE at school. This is due to neoliberal capitalist politics and that Physical Education should be viewed and discussed in schools in terms of corporal movement culture as knowledge historically constructed by men.